Effects of perioperative music therapy on pain, anxiety and hemodynamics in patients undergoing upper limb surgery - Ying, Tee May (2018)
Background: There are growing studies of music therapy recent years as a non-pharmacological method in perioperative management of anxiety and pain with promising result. This study was conducted to investigate the effect of perioperative religious-based music on pain, anxiety and hemodynamic parameters targeted specific in our local population. Objective: To examine the effectiveness of perioperative music intervention on pain, anxiety, and vital signs among patients undergoing upper limb surgery using religious-based music in Hospital Universiti Sains Malaysia (HUSM). Methods: A randomized single-blinded controlled clinical trial was conducted in the Operation Theatre in HUSM, Kelantan. 81 patients were recruited and randomly assigned to either Control (n = 40) or Music (n = 41) group respectively. Standard care was given to both Control and Music group. The Intervention group listened to patient-selected religious-based music preoperatively and throughout the surgery, while Control group were played with White noise sound preoperatively and throughout the surgery. Primary measures include pain score (at rest and dynamic), anxiety level, and vital signs, i.e. mean arterial pressure (MAP) and heart rate. Secondary outcomes include total fentanyl requirement intraoperatively, time to first morphine requirement after arrival in PACU, time to last morphine requirement in PACU and duration of stay in PACU before discharge. Results: The Music group showed remarkable reduction in anxiety level and MAP reduction within group (p<0.05 respectively). Statistically significant secondary outcomes include more than 50% reduction in total fentanyl requirement intraoperatively, with Control group 79.17μg (SD 45.87), while Music group 36.11μg (SD13.18) with p=0.01. Subjects in Music group have shorter duration of PACU stays compared to Control group (p=0.02). There was no significance difference between groups were identified in pain score and other secondary measures. Conclusion: The study findings provide new evidence to support the application of religious-based music intervention in reducing anxiety level, maintain more stable MAP intraoperatively and hastened discharge from PACU after upper limb surgery